Short-term memory impairment following recovery from systemic inflammation induced by lipopolysaccharide in mice - Morimoto, Kohei; Watanuki, Shu; Eguchi, Ryota; Kitano, Taisuke; Otsuguro, Ken-ichi (Frontiers in Neuroscience, 2023)
The relationship between neuroinflammation and mental disorders has been recognized and investigated for over 30 years. Diseases of systemic or peripheral inflammation, such as sepsis, peritonitis, and infection, are associated with increased risk of mental disorders with neuroinflammation. To elucidate the pathogenesis, systemic administration of lipopolysaccharide (LPS) in mice is often used. LPS-injected mice exhibit behavioral abnormalities with glial activation. However, these studies are unlikely to recapitulate the clinical pathophysiology of human patients, as most studies focus on the acute inflammatory response with systemic symptoms occurring within 24 hours of LPS injection. In this study, we focus on the effects of LPS on behavioral abnormalities following recovery from systemic symptoms and investigate the mechanisms of pathogenesis. Several behavioral tests were performed in LPS-injected mice, and to assess neuroinflammation, the time course of the morphological change and expression of inflammatory factors in neurons, astrocytes, and microglia were investigated. At 7 days post-LPS injection, mice exhibited short-term memory impairment accompanied by the suppression of neuronal activity and increases in morphologically immature spines. Glial cells were transiently activated in the hippocampus concomitant with upregulation of the microglial phagocytosis marker CD68 3 days after injection. Here we show that transient glial cell activation in the acute response phase affects neuronal activity and behavior following recovery from systemic symptoms. These findings provide novel insights for studies using the LPS-induced inflammation model and that will contribute to the development of treatments for mental disorders of this etiology.